EVALUATION OF THE EFFECTS OF DEVELOPMENT PLANS ON ECONOMIC DEVELOPMENT IN TURKEY FROM 1985 TO THE PRESENT - Kaya, H.; Uzun, Y. U. (Farabi Journal of Social Sciences, 2023)
This study analyzes the impact of development plans on Turkey’s economic growth from 1985 until the present. In an era where uncertainties are on the rise, and global balancing processes are witnessed frequently, development plans play an important role in fostering economic development. The study sheds light on Turkey’s interactions with other nations, its macroeconomic progress, social and economic advancements due to plan implementation, economic targets and expectations, democratization, and the rule of law. These factors are presented in a broader context that may differ from year to year with changing international dynamics. Keywords: development plans, economic development, Maxqda.